CD8+ T‐cell predominance in autoimmune glial fibrillary acidic protein astrocytopathy. (6th March 2021) - Yuan, Zhongmin; Li, Huilu; Huang, Lu; Fu, Congcong; Chen, Yaotang; Zhi, Cheng; Qiu, Wei; Long, Youming
Abstract: Background and objective: We aimed to report the pathological features of T lymphocytes in autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy (GFAP‐A). Methods: A retrospective pathological analysis of patients with GFAP‐A was performed. Results: Eight patients with GFAP‐immunoglobulin G (IgG) and pathological data were included. Their biopsy findings were similar, and all showed marked lymphocytic infiltration in the white matter, with perivascular predominance. The lymphocytic infiltration was predominantly composed of CD8 + T lymphocytes rather than CD4 + T lymphocytes, except in one patient who had overlapping positive myelin oligodendrocyte glycoprotein‐IgG. Unlike CD4 + T cells, CD8 + T cells were frequently observed adjacent to dystrophic neurons and astrocytes. There was also diffuse infiltration by CD68 + and CD163 + macrophages. CD8 + astrocytes were identified in two samples, but no CD4 + astrocytes were observed. Conclusions: A predominance of CD8 + T cells may be an important pathological and diagnostic feature in GFAP‐A.